MENGUPAS PRAKTIK PENGELOLAAN ADMINISTRASI KEUANGAN KANTOR KECAMATAN - Nora Erfianingtyas; Supri Wahyudi Utomo; Nur Wahyuning Sulistyowati (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2022)
The purpose of this study was to find out more about the financial administration management practices of the West District Head Office, West District, Magetan Regency. This type of qualitative research is descriptive and data obtained from interviews, observations, and documentation. The study resulted in the findings that the West Camat office in managing financial administration is in accordance with Permendagri No.64 of 2013 and the financial information compiled includes LRA; LO; balance sheet; LPE; and CaLK. The obstacles faced by the sub-district office are delays in the preparation and reporting of financial information, besides that the compilers of financial information at the West sub-district office are not from the accounting department. Abstrak Tujuan penelitian ini mengetahui lebih jauh praktik pengelolaan administrasi keuangan Kantor Camat Barat Kecamatan Barat Kabupaten Magetan. Jenis penelitian kualitatif deskriptif dan data didapatkan dari interview, pengamatan, dan dokumentasi. Penelitian menghasilkan temuan bahwa kantor Camat Barat dalam pengelolaan administrasi keuangan sudah sesuai Permendagri No.64 Tahun 2013 dan informasi finansial yang disusun meliputi LRA; LO; Neraca; LPE; dan CaLK. Hambatan yang dihadapi kantor camat adalah keterlambatan dalam penyusunan dan pelaporan informasi finansial, selain itu penyusun informasi finansial pada kantor Camat Barat bukan berasal dari jurusan akuntansi.